Ruang Publik Virtual sebagai Arena Kontrol Sosial: Analisis Sentimen Netizen pada Polemik Selebgram Jule - Fauza Syahiban; Dini Pristia; Nadira Syifa; Khairina Azira Br Purba; Wahyu Arif Syahputra (Jurnal Intervensi Sosial, 2025)
This research analyzes the function of the virtual public sphere as an arena for social control through a case study of the controversy surrounding celebrity influencer Julia Prastini (Jule). Employing a qualitative methodology with a case study approach and thematic sentiment analysis of netizen reactions, this study explores how digital interactions enforce social norms. The main findings reveal that netizen sentiment manifests as informal social control mechanisms, such as moral judgment (gossip/reprimand) and economic sanctions (cancel culture), which effectively uphold collective norms outside the formal legal framework. The analysis indicates that the virtual public sphere in this case exhibits a dual nature: it serves as a space for public discourse while simultaneously functioning as an arena for emotional and communal judgment, thereby challenging the idealistic Habermasian concept of a rational public sphere. This study concludes that in the digital era, social control has evolved, integrating social sanctions with tangible economic consequences driven by the attention economy.